If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6a = 36a Solving -6a = 36a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-36a' to each side of the equation. -6a + -36a = 36a + -36a Combine like terms: -6a + -36a = -42a -42a = 36a + -36a Combine like terms: 36a + -36a = 0 -42a = 0 Divide each side by '-42'. a = 0 Simplifying a = 0
| y=2x-5x+7 | | 2.9r=-5.7t-5 | | x-(-14)=-11 | | 5y-9=7+y | | 60-what+10=20 | | 5=1-4(-5) | | 3m-7=m-13 | | 3x+9x+5=17 | | 4-5p=8 | | 2(X+8)+5x-9=3(X+2)+4(2x+9)-5(3x+8)+25-12x | | 3x^2=89 | | 5v^2-8v-21=0 | | 10y-21=7y | | 4b+7=15 | | 7x+11=x-2510 | | 2x+5=11yforx | | -38=-2n | | 3x+29y=-17 | | x/4-(4x-10)/5=7/10x | | p/3=3(y-5X)/2 | | [5x+3]+10=7 | | 9(3x+10)+20=50 | | 655=v-543 | | 2x+5=11forx | | 3y-2+y+50=5+6y+45-4y | | p/5=3(y-5X)/2 | | X+(x+7)=49 | | 2(z+.5)=8-z | | 7x-4x-3=118 | | 5+12x-2=8x+27-2x | | 3(X+8)=X-3 | | y-29=38 |